Pertussis immunization during pregnancy: results of a cross-sectional study among Italian healthcare workers - Licata, Francesca; Romeo, Marika; Di Gennaro, Gianfranco; Citrino, Emma Antonia; Bianco, Aida (Frontiers in Public Health, 2023)
Background: To assess if Italian healthcare workers recommend the reduced antigen content tetanus-diptheria-acellular pertussis vaccination (Tdap) to pregnant people, as well as what variables could predict their decision to advice and recommend immunization to pregnant people. Methods: This cross-sectional study took place between August 2021 and June 2022 in a sample of obstetricians-gynecologists, midwives, and primary-care physicians in three regions of Southern Italy. A self-administered questionnaire was used to gather the data. Results: The results showed 91.3% participants knew that receiving the Tdap vaccine during pregnancy protects against pertussis both the mother and the newborns before active immunization. Only 68.9% knew that the Tdap vaccination has to be administered during the third trimester of gestation. Small but still significant proportion of participants 14.7% believed that the potential risks of vaccines administered during pregnancy outweighed the benefits. An improvable proportion of and healthcare workers regularly provided information 71.8% and recommended 81% Tdap vaccination to pregnant people. Conclusion: Educational and informative interventions to improve healthcare workers’ knowledge about the importance of the Tdap vaccine and their communication skills to properly counsel pregnant people are needed. Beyond vaccine recommendations, how well immunization strategies are implemented in real-world situations impacts on vaccination uptake. So, during routine doctor visits, expecting moms must have easy access to vaccines. Prenatal immunizations should become common practice, and there should be no conceptual doubt about vaccinations among healthcare workers in order to safeguard pregnant people and their unborn children from vaccine preventable diseases.